2022
DOI: 10.1136/bmjopen-2021-059000
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for automatic brain tumour segmentation on MRI: evaluation of recommended reporting criteria via a reproduction and replication study

Abstract: ObjectivesTo determine the reproducibility and replicability of studies that develop and validate segmentation methods for brain tumours on MRI and that follow established reproducibility criteria; and to evaluate whether the reporting guidelines are sufficient.MethodsTwo eligible validation studies of distinct deep learning (DL) methods were identified. We implemented the methods using published information and retraced the reported validation steps. We evaluated to what extent the description of the methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This makes it difficult to evaluate different networks accurately and fairly, particularly when the necessary information to replicate the networks and results is not reported. Gryska et al [45] even caution about the difficulties in replicating segmentation models and argue that established reproducibility criteria do not adequately emphasize the importance of describing the preprocessing chain. They conclude that a detailed description of the entire preprocessing chain is necessary to establish solid evidence of the generalizability of segmentation methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it difficult to evaluate different networks accurately and fairly, particularly when the necessary information to replicate the networks and results is not reported. Gryska et al [45] even caution about the difficulties in replicating segmentation models and argue that established reproducibility criteria do not adequately emphasize the importance of describing the preprocessing chain. They conclude that a detailed description of the entire preprocessing chain is necessary to establish solid evidence of the generalizability of segmentation methods.…”
Section: Discussionmentioning
confidence: 99%
“…In different approaches, Gryska et al [45] replicate two segmentation models (3D dual-path CNN and 2D single-path CNN), seeking to determine the reproducibility and replicability of the studies. The study found that one of the two methods was successfully reproduced, but the second method could not be reproduced due to insufficient description of the preprocessing pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Specifying preprocessing steps is also important for ensuring the reproducibility of the results. Choices in preprocessing technique can substantially affect the properties of the resulting model, including accuracy and interpretability ( 135 , 136 ).…”
Section: Module 4: Data Preprocessingmentioning
confidence: 99%